What we are learning on HTLV-1 pathogenesis from animal models - Duc Dodon, Madeleine; Villaudy, Julien; Gazzolo, Louis; Haines, Robyn; Lairmore, Michael (Frontiers in Microbiology, 2012)
Isolated and identified more than 30 years ago, Human T-cell Leukemia Virus type 1 (HTLV-1) is the etiological agent of adult T-cell leukemia/lymphoma (ATL), an aggressive lymphoproliferative disease of activated CD4+ T cells, and other inflammatory disorders such as HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). A variety of animal models have contributed to the fundamental knowledge of HTLV-1 transmission, pathogenesis and to the design of novel therapies to treat HTLV-1 associated diseases. Small animal models (rabbits, rats, mice) as well as large animal models (monkeys) have been utilized to significantly advance characterization of the viral proteins and of virus-infected cells in the early steps of infection, as well as in the development of leukemogenic and immunopathogenic processes. Over the past two decades, the creation of new immuno-compromised mouse strains that are robustly reconstituted with a functional human immune system (HIS) after being transplanted with human tissues or progenitor cells has revolutionized the in vivo investigation of viral infection and pathogenesis. Recent observations obtained in HTLV-1-infected humanized HIS mice that develop lymphomas provide the opportunity to study the evolution of the proviral clonality in human T cells present in different lymphoid organs. Current progress in the improvement of those humanized models will favor the testing of drugs and the development of targeted therapies against HTLV-1-associated diseases.